ATMA NIRBHAR BHARAT: AN ELABORATE STUDY INCLUDING CASES FROM NORTHERN AND SOUTHERN INDIA - Kumar, Ramesh; Bindlish, Mohit; Garg, Rajesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The suspension of business operations, the closure of industries, and the nationwide lockdown, which lasted for over three months during the pandemic, severely affected the flow of cash and capital in the market, creating an economic environment fraught with uncertainty. In response to this crisis, the Reserve Bank of India (RBI) took proactive measures early on, employing a series of monetary policy interventions aimed at restoring liquidity and supporting financial stability. These measures included reductions in key policy rates and a range of initiatives designed to ensure that credit continued to flow to sectors that were most affected by the lockdowns, such as small businesses, agriculture, and the informal economy. Despite these efforts, it was evident that more comprehensive and targeted actions were required to mitigate the far-reaching economic repercussions of the crisis. In this context, the Government of India unveiled the Atmanirbhar Bharat (Self-Reliant India) initiative, a broad, multi-faceted economic stimulus package aimed at reviving the economy and addressing both immediate and long-term challenges. Atmanirbhar Bharat was not just an economic strategy but a vision for strengthening India’s resilience and self-sufficiency in critical sectors. The initiative was designed to provide relief to businesses and individuals, stimulate domestic production, and reduce dependency on external markets for essential goods and services. Alongside the economic measures, the government also introduced several legal and social reforms that were intended to streamline business processes, improve the ease of doing business, and address labor and social welfare issues that were intensified during the pandemic. The aim of this study is to critically analyze the Atmanirbhar Bharat initiative, breaking it down into its core components and assessing its potential impact on India's liquidity situation, legal framework, and social reforms.